Karakteristik, Pengetahuan, dan Persepsi Masyarakat Tentang Skrining Hipotiroid Kongenital - Tiya Purnama Dewi; Ni Wayan Manik Parwati; Ni Komang Sri Ariani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2025)
Congenital Hypothyroid Screening is a screening test performed on newborns with the goal to detect congenital hypothyroidism earlier. In May 2023, 10 newborns (23.2%) participated in CHS according to a research study conducted at Public Health Center I Kubutambahan. CHS implementation in Indonesia is profoundly low at 4.6%, and in Bali Province is 5.2%.To determine knowledge and perception of society about congenital hypothyroid screening in the area of Kubutambahan Public Health Center I. This study employed descriptive qualitative design with cross sectional approach. There were 379 respondents selected for the sample of this study by using a combination of non-probability (purposive sampling) and probability (cluster sampling) methods. The data were collected by using questionnaire which was distributed traditionally. The data were analyzed by using univariate analysis. From 379 respondents, 92.9% are female, with 90.5% aged between 19 and 44 years old, and the majority, which is 62.3%, were unemployed. There were 68.9% respondents had good knowledge about CHS and there were 100% had a good perception of CHS. Around 85.2% of participants had incorrect answer about time of CHS sampling, and there were 79.6% of participants experienced anxiety about CHS implementation.For the purpose to increase CHS coverage in Indonesia, it is expected that all stakeholders including health professionals will expand their knowledge about CHS.